Pengaruh Gaya Kepemimpinan Terhadap Keberlangsungan Bisnis Melalui Budaya Organisasi Pada Karyawan Generasi Milenial Di Kabupaten Bekasi - Warja, Ade Agung Gunawan; Setyaningrum, Retno Purwani (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the effect of leadership style on business sustainability, as well as the mediating role of organizational culture in the relationship. This study involved 96 millennial generation employees in Bekasi Regency as respondents with a sample size calculation using the Lemeshow formula. Data were collected through questionnaires and analyzed using SmartPLS 3.0. The results showed that leadership style affects business sustainability, leadership style affects organizational culture, organizational culture affects business sustainability, and leadership style affects business sustainability mediated by organizational culture.